Effect of Ethnicity on the Speaking Fundamental Frequency Values of Indians vis-a-vis Caucasians, Afro-Americans and Mongoloids: A Forensic Phonetic Perspective - Akoju, Dr. Swapna; Suneetha Didla, Dr. Grace (International Journal of English Literature and Social Sciences (IJELS), 2020)
It is established in the forensic literature that the ethnic background of an individual has a robust bearing on one’s speaking fundamental frequency (SFF). The aim of this study is to record the SFF values of Indian adult speakers and compare the SFF of Indian speakers with those of existing data on other ethnic groups like Caucasians, Afro-Americans and Mongoloids in order to examine the effect of ethnicity on SFF. In addition, it is also to observe if language and mode of speech has any bearing on the SFF values. The study included 20 Indian speakers whose ages ranged from 21 to 40 years. A read passage and spontaneous speech in two languages (Telugu and English) constituted the text. PRAAT software was used to extract SFF values and a comparison was made between the obtained SFF values of Indian speakers and those drawn from other studies on three ethnic groups: Caucasians, Afro-Americans and Mongoloids. Results indicate that the Indian speakers (both male and female) exhibited a marginally higher pitch (on an average) compared to those of the other three ethnicities.